The Influence of Debt Policy, Profit Growth and Inventory Turnover on Firm Value Moderated Firm Size - Hermanto Hermanto; Eneyza Fatmalia Sari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to examine the influence of debt policy, profit growth and inventory turnover towards firm value with moderated by firm size. The information in this research was obtained from the financial report in the food and beverage sub sector manufacturing industry that listed on the IDX with the purposive sampling test method. The research period was taken for 6 years by resulted 144 data from 24 food and beverage sub sector entities. The research method uses multiple linear regression analysis with secondary data types. The research shows that simultaneously the three independent variables have an influence on the dependent variables. Partially debt policy and profit growth have a positive effect on the firm value, but the turnover of inventory has a negative influence on the firm value. The results of this researchs show that the three independent variables have a significant influence against the dependent variable moderated by the firm size. Moderated by firm size, debt policy and profit growth have a negative influence to the firm value, while inventory turnover has a positive influence to the firm value.